What do animal models tell us about the role of EBV in the pathogenesis of multiple sclerosis? - Hassani, Asma; Khan, Gulfaraz (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is a chronic disease of the central nervous system (CNS), marked primarily by demyelination, inflammation, and neurodegeneration. While the prevalence and incidence rates of MS are on the rise, the etiology of the disease remains enigmatic. Nevertheless, it is widely acknowledged that MS develops in persons who are both genetically predisposed and exposed to a certain set of environmental factors. One of the most plausible environmental culprits is Epstein-Barr virus (EBV), a common herpesvirus asymptomatically carried by more than 90% of the adult population. How EBV induces MS pathogenesis remains unknown. A comprehensive understanding of the biology of EBV infection and how it contributes to dysfunction of the immune system and CNS, requires an appreciation of the viral dynamics within the host. Here, we aim to outline the different animal models, including nonhuman primates (NHP), rodents, and rabbits, that have been used to elucidate the link between EBV and MS. This review particularly focuses on how the disruption in virus-immune interaction plays a role in viral pathogenesis and promotes neuroinflammation. We also summarize the effects of virus titers, age of animals, and route of inoculation on the neuroinvasiveness and neuropathogenic potential of the virus. Reviewing the rich data generated from these animal models could provide directions for future studies aimed to understand the mechanism(s) by which EBV induces MS pathology and insights for the development of prophylactic and therapeutic interventions that could ameliorate the disease.